Melatonin prevents gentamicin‐induced testicular toxicity and oxidative stress in rats. (4th November 2013) - Kim, S.‐H.; Lee, I.‐C.; Baek, H.‐S.; Shin, I.‐S.; Moon, C.; Kim, S.‐H.; Yun, W.‐K.; Nam, K.‐H.; Kim, H.‐C.; Kim, J.‐C.
Summary This study investigated the protective effects of melatonin (MT) against gentamicin (GM)‐induced testicular toxicity and oxidative damage in rats. GM (100 mg kg−1) was injected intraperitoneally (i.p.) to rats for 6 days. MT (15 mg kg−1) was administered i.p. to rats for 6 days at 1 hr after the GM treatment. GM caused a decrease in prostate and seminal vesicle weights, sperm count and sperm motility. Histopathological examination showed various morphological alterations in the testis, characterised by degeneration of spermatogonia/spermatocytes, decrease in the number of early spermatogenic cells and vacuolisation. In addition, an increased malondialdehyde concentration and decreased glutathione content and glutathione reductase, catalase and glutathione‐S‐transferase activities were found in the testis. In contrast, MT treatment significantly attenuated the testicular toxicity of GM, including decreased reproductive organ weights, sperm count, and sperm motility and increased histopathological alterations. MT also had an antioxidant benefit by decreasing the lipid peroxidative product malondialdehyde and increasing the level of the antioxidant glutathione and the activities of antioxidant enzymes in the testis. These results indicate that MT prevents testicular toxicity induced by GM in rats, presumably due to its potent antioxidant activity, and its ability to inhibit lipid peroxidation, and restore antioxidant enzyme activity.